Urodynamic values role for females with different types of urinary incontinence - Zane Pilsetniece; Egils Vjaters (Russian Open Medical Journal)
Aim — The aim of this study was to analyse how conventional urodynamic values differ between females with specific types of urinary incontinence (UI). Material and Methods — Cross-sectional study enrolled 666 females with UI. Based on patient history and questionnaires they were divided into three groups: stress (SUI), mixed (MixUI) and urgency (UUI). Physical investigation and urodynamics were performed. The continuous factors: age and urodynamic data were evaluated using Multinomial regression and ANOVA test using SUI, MixUI, UUI as outcome groups. Results — Analysing urodynamic parameters significant difference between at least two groups was shown by the cystometric capacity and maximum flow rate: both highest in the SUI group; residual urine, opening detrusor pressure, maximum urethral closure pressure at rest, functional urethral length at rest: all highest in the UUI group. Mainly all urodynamic data showed significant difference between SUI/UUI, and MixUI/UUI groups, while difference between SUI/MixUI were not significant. Conclusions — Most of urodynamic data for MixUI group patients do not differ from SUI group. UDS parameters like: maximum flow rate, residual urine, opening detrusor pressure, maximum urethral closure pressure at rest, functional urethral length at rest can help to distinguish SUI and MixUI groups from UUI group.